Pengaruh Tata Ruang Kantor Terhadap Kinerja Pegawai Pada Kantor Bappeda Litbang Kota Ambon - Ambarwati Soetiksno; Febiyola Wijaya; Isak Akasian (Jurnal Administrasi Terapan, 2023)
Office layout is the arrangement of office space such as arranging office furniture and equipment on the available floor area to provide facilities for employees / employees to carry out their work activities properly. Bappeda, is a regional technical institution in the field of research and regional development planning led by a head of an agency who is under and responsible to the Governor / Regent / Mayor through the Regional Secretary. The problems faced by the Ambon City Research and Development Planning Agency Office are: the type of open space layout without any divides between employees in working based on the number of employees and to support the smoothness of employees, some office space has not maximized office space in the application of good office layout. Some work fields have a narrow space so that the arrangement is too pile up, even tables and chairs that have not been arranged according to the conditions of the narrow room so that they are less pleasing to the eye can result in less comfortable employees in the room. This can cause discomfort and interfere with concentration at work, then reduce the speed at work and result in fatigue due to the mismatch of the required work flow. It was found that there was an uncluttered arrangement of part of the workspace that seemed cluttered by files, uneven placement of the Airconditioner (AC) so that some employees complained of feeling hot and stuffy. This study aims to determine: the effect of office layout on employee performanceThis research is a quantitative research supported by descriptive analysis. The data collection method is by using a questionnaire. The population in this study amounted to 36 with a sample of 36 people. The sampling technique used was saturated samples. From the results of statistical research, office layout has a positive and significant effect on employee performance at the Ambon City Research and Development Planning Agency Office. This is evidenced by the coefficient value of the office layout variable of 4.146, which is greater than t table of 2.032244 and the significant value of the performance variable of 0.00 is less than 0.05, which means that with good office layout, employee performance will increase. Meanwhile, there is a correlation coefficient value x on the y variable of 0.579 with a moderate relationship. Meanwhile, to get a high or very strong relationship, the variable X (office layout) and the y variable (employee performance) must have a correlation coefficient of 1.00 so it can be found that there is a very high or very strong relationship between variable X ( office layout) and variable Y (employee performance). And the coefficient of determination (R square) Office layout has an effect of 33.6% on employee performance. and suggestions, the Ambon City Research and Development Planning Agency Office be able to implement a good office layout design, in order to help overcome several problems related to existing workspace layouts. That way, employee work productivity can also be increased due to employee satisfaction and comfort with the work space used, as well as the ease in the process of carrying out work.The Ambon City Research and Development Planning Agency Office should arrange or rearrange the existing office layout according to the size of the space, so that the office space looks good in the eyes and the activity process of the employees is more comfortable and smooth at work. Keywords: Office Layout, Employee Performance.